Effects of plant biomass on nitrate removal and transformation of carbon sources in subsurface-flow constructed wetlands - Wen, Yue; Chen, Yi; Zheng, Nan; Yang, Dianhai; Zhou, Qi (Bioresource technology, 2010)
Denitrification is strongly dependent on carbon quantity and quality in most constructed wetlands (CWs). In this study, four batch CWs were designed, and were fed with nitrate-dominated water to investigate nitrate removal affected by plant and external cattail litter with or without alkali pretreatment. The results showed that the unit with plant and alkali-pretreated litter was more efficient in the initial stage whereas unit with plant and unpretreated litter was superior to other units in the middle and terminal stages. Plant accounted for less than 37% of the nitrate removal in biomass-up added CWs. The different nitrate removal rates were found to be greatly affected by the composition of the plant biomass as well as the quantity and quality of the available organic matters. It was also observed that plant biomass degradation over the period of this study resulted in various N species and concentrations in effluent.